Caracterizações física e química de resíduos sólidos da cajucultura e avaliação do potencial energético em processos de conversão térmica - Tavares, Priscilla Torquato (2016)
The exponential increase in energy demand and the growing need for sustainable energy production require diversification of energy sources. Biomass has stood out due to their economic and physicochemical particulars, and may be considered as the energy source of the future. Agricultural waste is a form of biomass suitable for energy production. The cultivation and beneficiation of cashew generated, in 2015, between 1.4 and 1.5 million tons of cashew nut shell (CNS) and between 4.2 and 5.0 million tons of cashew apple bagasse (CAB) (IBGE, 2016). Therefore, the use of these waste for energy purposes would reduce disposal issues of these and could substitute others fuels in industries. The objective of this study is to verify the possibility of using solid waste from cashew culture as an alternative and renewable energy source in thermal conversion processes, characterizing them physically and chemically (immediate analysis, elemental analysis, density measurement, calculation of calorific value, SEM and XRF), and verifying the probability of ash melt. Furthermore, the thermal behavior of the residues was evaluated by thermogravimetric analysis carried out in inert and oxidizing atmosphere in order to analyze the processes of pyrolysis and combustion, respectively. The thermal behavior of waste was evaluated by thermal gravimetric analysis. CNS is more energetic than the CAB, because despite having the same H/C ratio (0.13), CNS has lower O/C ratio (0.67) than CAB (0.89). The N and S found were high for both CAB (3.59 and 0.98%, respectively) and CNS (0.85% and 0.89 respectively), indicating the release of pollutants during thermochemical conversion which must be contained. The CAB and the CNS showed a high density, high volatile matter content and low ignition temperature, 167 ºC and 199 ºC respectively, as well as low ash content, 3.55 and 2.16% for CAB and CNS, respectively. The pyrolysis curve showed that there were three major peaks for CNS, relating to the degradation of hemicellulose, cellulose and lignin fraction, respectively; while for CAB it was observed the presence of a well defined peak at 300 ºC, representing the superposition of simultaneous degradation of lignocellulosic components. During the combustion, there are three peaks for CNS, which indicates loss of hemicellulose, cellulose and lignin, predominantly, and for CAB there were two predominant peaks, corresponding to the loss of the hemicellulose and cellulose to the oxidation of the cellulose. In conclusion, it was found that the solid wastes in question have potential to be used as an alternative and renewable energy source and may collaborate with energy diversification, giving a sustainable disposal for cashew cultivation residues.